2015
DOI: 10.1111/1475-6773.12393
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Job Insecurity on Health Care Utilization: Findings from a Panel of U.S. Workers

Abstract: Objective. To examine the impacts of job insecurity during the recession of 2007-2009 on health care utilization among a panel of U.S. employees. Data Sources/Study Setting. Linked administrative and claims datasets on a panel of continuously employed, continuously insured individuals at a large multisite manufacturing firm that experienced widespread layoffs (N = 9,486). Study Design. We employed segmented regressions to examine temporal discontinuities in utilization during 2006-2012. To assess the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…53 Compared with individuals in retirement, individuals with employment may be hindered from seeking health care, including cancer screening, because of a lack of sick leave, the added burden of taking days off work, and/ or the fear of negative occupational outcomes caused by perceptions of job insecurity. 54,55 This study had several limitations. The HCPS is a cross-sectional data set, so we could not make causal inferences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…53 Compared with individuals in retirement, individuals with employment may be hindered from seeking health care, including cancer screening, because of a lack of sick leave, the added burden of taking days off work, and/ or the fear of negative occupational outcomes caused by perceptions of job insecurity. 54,55 This study had several limitations. The HCPS is a cross-sectional data set, so we could not make causal inferences.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, the greatest proportion of nonparticipants in the labor force reported retirement as the reason for that status . Compared with individuals in retirement, individuals with employment may be hindered from seeking health care, including cancer screening, because of a lack of sick leave, the added burden of taking days off work, and/or the fear of negative occupational outcomes caused by perceptions of job insecurity …”
Section: Discussionmentioning
confidence: 99%
“…For example, during the Great Recession of 2008, both in the USA and Europe, job loss was associated with increased depressive symptoms among older workers,11 partly reflecting the uncertainty around retirement plans, the fear of negative effects of withdrawing from social networks, loss of a social role and social stigma and psychological distress 18–25. Likewise, the literature suggests that chronic job insecurity leads to poorer self-rated health reports and minor psychiatric morbidity (which appear to be long term and remain even after uncertainty has decreased)26 and an increase in healthcare use 27. If the Brexit vote increased the perception of job insecurity, we would expect some of these symptoms to emerge.…”
Section: Introductionmentioning
confidence: 98%
“…Alternately, poverty is also associated with a higher burden of disease and chronic stress, potentially resulting in greater utilization of specific types of services such as emergency care, depending on insurance coverage . For example, prior studies that exploit the discrete shock created by the Great Recession have found that financial and job insecurity may have resulted in foregone outpatient care, as well as increased utilization of and expenditures on emergency and mental health services …”
Section: Introductionmentioning
confidence: 99%